Beclin1 Haploinsufficiency accentuates second-hand smoke exposure -induced myocardial Remodeling and contractile dysfunction through a STING-mediated mechanism. (November 2020) - Liu, Fangpeng; Liu, Yandong; Zhuang, Zhiqiang; Ma, Jipeng; Xu, Xihui; Zhang, Wenjing; Peng, Hu; Yang, Lifang; Zhang, Wei; Pei, Zhaohui; Ren, Jun
Abstract: Second-hand smoking evokes inflammation and cardiovascular diseases. Recent evidence has revealed a pivotal role for deranged autophagy in smoke exposure-induced cardiac anomalies. This study evaluated the impact of haploinsufficiency of the mTOR-independent autophagy protein Beclin1 on side-stream smoke exposure-induced cardiac anomalies and mechanism(s) involved. Adult WT and Beclin1 haploinsufficiency (Becn +/− ) mice were exposed to cigarette smoke for 1 h daily for 90 days. Echocardiographic, cardiomyocyte function, intracellular Ca 2+, autophagy, mitophagy, apoptosis and inflammation were examined. DHE staining was employed to evaluate O2 − level. Our data revealed that Beclin1 deficiency exacerbated smoke exposure-induced myocardial anomalies in geometry, fractional shortening, cardiomyocyte function, intracellular Ca 2+ handling, TEM ultrastructure, and inflammation along with pronounced apoptosis and O2 − production. Side-stream smoke provoked excessive autophagy/mitophagy, mtDNA release, and activation of innate immune response signals cyclic GMP-AMP synthase (cGAS) and its effector – stimulator of interferon genes (STING), the effect was abolished or unaffected by Becn haploinsufficiency. STING phosphorylation was overtly promoted by smoke exposure in Becn +/− mice. Smoke exposure also suppressed phosphorylation of mTOR although it facilitated that of ULK1 in both groups. In vitro data revealed that inhibition of cGAS or STING failed to affect smoke extract-induced mitophagy although they abrogated smoke extract-induced cardiomyocyte dysfunction except cGAS inhibition in Becn +/− mice. These data suggest that Beclin1 is integral in the maintenance of cardiac homeostasis under side-stream smoke exposure via a STING-mediated mechanism. Graphical abstract: Unlabelled Image Highlights: Side-stream smoke exposure provokes cardiac structural and functional anomalies. Beclin1 haploinsufficiency accentuates smoke exposure-induced cardiac dysfunction. Beclin1 deficiency suppresses smoke exposure-induced autophagy/mitophagy. Beclin1 deficiency diminishes autophagy-mediated STING dephosphorylation Ser 366 . Targeting STING signaling offers promises in smoking-induced cardiac anomalies.